2016
DOI: 10.1016/j.celrep.2016.10.080
|View full text |Cite
|
Sign up to set email alerts
|

LYVE1 Marks the Divergence of Yolk Sac Definitive Hemogenic Endothelium from the Primitive Erythroid Lineage

Abstract: The contribution of the different waves and sites of developmental hematopoiesis to fetal and adult blood production remains unclear. Here, we identify lymphatic vessel endothelial hyaluronan receptor-1 (LYVE1) as a marker of yolk sac (YS) endothelium and definitive hematopoietic stem and progenitor cells (HSPCs). Endothelium in mid-gestation YS and vitelline vessels, but not the dorsal aorta and placenta, were labeled by Lyve1-Cre. Most YS HSPCs and erythro-myeloid progenitors were Lyve1-Cre lineage traced, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 57 publications
5
58
0
Order By: Relevance
“…Taken together, these results strongly suggest that epigenetic priming by Dot1l in LEC progenitors, including both Tie2(+) and c-Kit(+) cells, during LEC differentiation is essential for the formation of mesenteric lymphatics. Moreover, given that HEs from the yolk sac are Lyve1 positive, whereas HEs from AGM are Lyve1 negative 41 , our findings also imply that Dot1l function in yolk-sac-derived HEs may have little effect on mesenteric LEC differentiation.…”
Section: Dot1l Function In C-kit(+) Hemogenic Ecs Is Required For Mesmentioning
confidence: 53%
“…Taken together, these results strongly suggest that epigenetic priming by Dot1l in LEC progenitors, including both Tie2(+) and c-Kit(+) cells, during LEC differentiation is essential for the formation of mesenteric lymphatics. Moreover, given that HEs from the yolk sac are Lyve1 positive, whereas HEs from AGM are Lyve1 negative 41 , our findings also imply that Dot1l function in yolk-sac-derived HEs may have little effect on mesenteric LEC differentiation.…”
Section: Dot1l Function In C-kit(+) Hemogenic Ecs Is Required For Mesmentioning
confidence: 53%
“…In addition, like HSC, EMP require Runx1 for their emergence, providing further evidence that EMP emerge via an endothelial-to-hematopoietic transition (35, 36). Recent studies indicate that EMP and some HSC, but not primitive erythroid cells, emerge from LYVE-1+ endothelium (37). These results point to the distinct developmental origins of primitive- and EMP-derived hematopoiesis from posterior mesoderm (Figure 1).…”
Section: Ontogeny Of Erythropoiesismentioning
confidence: 99%
“…Although several studies suggested that HSCs may be produced from the YS [15][16][17][18] , engraftment experiments in avian models and transplantation studies in mice indicated an intraembryonic origin of HSCs [19][20][21][22] To date no explanation has been found to account for the difference in output of EHT that occurs in the YS versus AGM. It is not known whether there are intrinsic differences between the HEC of the two tissues or whether cell-extrinsic factors produced in the microenvironment drive HSC output in the AGM.…”
Section: Introductionmentioning
confidence: 99%